Examining the impact of different social class mechanisms on health inequalities: A cross-sectional analysis of an all-age UK household panel study. (November 2022) - Whitley, Elise; McCartney, Gerard; Bartley, Mel; Benzeval, Michaela
Abstract: Background: Socioeconomic inequalities are well established across health, morbidity and mortality measures. Social class theory describes how social groups relate, interact and accrue advantages/disadvantages relative to one another, with different theorists emphasising different dimensions. In the context of health inequalities, different social class measures are used interchangeably to rank population groups in terms of health rather than directly exploring the role of social class in creating inequalities. We aim to better understand how four distinct social class mechanisms explain differences in a range of self-reported and biological health outcomes. Methods: We use data from the UK Household Longitudinal Study, a representative population survey of UK adults, to identify measures pertaining to Early years, Bourdieusian, Marxist, and Weberian social class mechanisms. Using logistic and least-squares regression we consider the relative extent to which these mechanisms explain differences in health (Self-reported health, SF12 Physical (PCS) and Mental (MCS) Component Scores, General Health Questionnaire; N = 21, 446) and allostatic load, a biomarker-based measure of cumulative stress (N = 5003). Results: Respondents with higher social position according to all social class measures had better self-rated, physical and mental health, and lower allostatic load. Associations with Marxist social class were among the strongest (e.g. Relative Index of Inequality for very good/excellent self-rated health comparing highest versus lowest Marxist social class: 4.96 (4.45, 5.52), with the Weberian measure also strongly associated with self-rated (4.35 (3.90, 4.85)) and physical health (Slope Index of Inequality for SF12-PCS: 7.94 (7.39, 8.48)). Health outcome associations with Bourdieusian and Marxist measures were generally stronger for women and older respondents, and physical health associations with all measures were stronger among those aged 50+ years. Conclusions: The impact of social class on health is multi-faceted. Policies to reduce health inequalities should focus more on unequal capital ownership, economic democracy and educational inequalities, reflecting Marxist and Weberian mechanisms. Highlights: We explore the impact of four distinct Social Class theories on health inequalities. There are substantial inequalities in health and stress according to all measures. Inequalities encompassing wealth and educational advantage are particularly marked.